Discovering Cell-Adhesion Peptides in Tissue Engineering: Beyond RGD. Issue 4 (April 2018) - Huettner, Nick; Dargaville, Tim R.; Forget, Aurelien
Abstract : As an alternative to natural extracellular matrix (ECM) macromolecules, cell-adhesion peptides (CAPs) have had tremendous impact on the design of cell culture platforms, implants, and wound dressings. However, only a handful of CAPs have been utilized. The discrepancy in ECM composition strongly affects cell behavior, so it is paramount to reproduce such differences in synthetic systems. This Opinion article presents strategies inspired from high-throughput screening techniques implemented in drug discovery to exploit the potential of a growing CAP library. These strategies are expected to promote the use of a broader spectrum of CAPs, which in turn could lead to improved cell culture models, implants, and wound dressings. Highlights: Hydrogel materials with mechanical and biological properties mimicking the ECM are used to organize different cell types into functional tissue. As an alternative to animal-derived ECM proteins, CAPs such as the AA sequence RGD can control the adhesion of cells onto synthetic materials. Synthetic biocompatible hydrogels do not present specific CAPs that can precisely control cell fate and function. Quick and high-yielding conjugation reactions can link biological signals to synthetic hydrogels in robotized liquid handling systems under physiological conditions. Automatically fabricated artificial ECM can rapidly create and test cell microenvironments. These platforms can decipher the role of RGD-alternative CAPs, more quickly identify CAPs to control cell function, and extend our control of cell adhesion on synthetic materials.